A factor model approach to nowcasting Danish GDP - Adrian Michael Bay Schmith; Erik Grenestam (Danmarks Nationalbank, 2021)
This memo documents a nowcasting model for Danish GDP used during the economic crisis related to the outbreak of COVID-19. During this crisis, the model provided timely and more accurate nowcasts than a simple model. To improve the timeliness of nowcasts we make use of new high-frequency indicators.
Keywords: 330; Bruttoinlandsprodukt; Wirtschaftsprognose; Prognoseverfahren; Dänemark